[3120+1kbdel8.6kb]+[p.N1303K] GENOTYPE IN AN EMIRATI CYSTIC FIBROSIS PATIENT: INDICATION OF A FOUNDER MUTATION IN PALESTINIAN ARABS - Saleheen, Danish; Frossard, Philippe M.; Girodon, Emmanuelle (Journal of Ayub Medical College Abbottabad, 2006)
Cystic fibrosis (CF) is the most common life-limiting autosomal recessive disorder in Caucasian population. The disease was initially considered to be rare in Middle Eastern countries. 95% of CF in Emirati families is due to two mutations only - p.S549R(T>G) and p.F508del. We report here the case of a patient referred to CF and Respiratory Clinic at Tawam Hospital for cystic fibrosis transmembrane regulator (CFTR) gene screening to ascertain the diagnosis of CF, who was found to carry a unique genotype, signifying the importance of retrieving ancestral histories of patients with monogenic disorders Keywords: Cystic Fibrosis, autosomal recessive disorder, Genotype